Respostas

2013-12-08T13:20:40-02:00
A) x2 + x - 2 = 0
b2 - 4ac =
1 + 8 = 9 raíz de delta = 3
x = -b + ou - raiz de delta / 2a
x = -1 + ou - 3 / 2
x = -2 ou 1

b) 2x2 + 7x + 5 = 0
raiz de delta = 3
x = -7 + ou - 3/4
x = -1 ou -5/2
2013-12-08T13:36:27-02:00
A) x² + x - 7 = 5 
x² + x - 7 - 5 = 0
x² + x - 12 = 0
a = 1           b = 1                  c = - 12
∆ = b² - 4 . a . c 
∆ = 1² - 4 . 1 (- 12)
∆ = 1 + 48
∆ = 49
 x =  - b + √∆
       ----------------  
             2
a

x = - 1 + √49
      ----------------
          2 . 1
x = - 1 
+ 7
      -----------
           2
x' = - 1 + 7 
           2
x' = 6 : 2
x' = 3

x" = - 1 - 7 
          2
x" = - 8 : 2
x" = - 4
Resposta: {3; - 4}

B) 2x² = - 5 - 7x
2x² + 5 + 7x = 0
a = 2                b = 7                 c = 5
∆ = b² - 4 . a . c 
∆ = 7² - 4 . 2 . 5
∆ = 49 - 40
∆ = 9
 x =  - b + √∆ 
       ----------------  
             2a 
x = - 7 + √9
      --------------
          2 . 2
x = - 7 + 3
     -------------
           4
x' = - 7 + 3 
          4
x' = - 4 : 4
x' = - 1

x" = - 7 - 3 
          4
x" = - 10 : 4
x" = - 2,5
Resposta: {- 1; - 2,5}
1 5 1